Determining Factors For The Accuracy Of Diagnosis Codes Using ICD-10 In Obstetric Cases: Riview Systematics - Wibowo, Syifa Sofia (Health Science UDINUS, 2023)
Medical record coder has complete duties, responsibilities, authority and rights to carry out medical record service activities in health service units. The accuracy of the disease diagnosis code is crucial, the accuracy of the diagnosis code will affect the claim for treatment costs, the allocation of health resources and the accuracy of hospital statistical data. This research systematically reviews articles uses the PRISMA diagram to help sort articles to use, also have criteria: research data is data from Indonesia, uses Indonesian or English, the article was published 2018-2023, the article can be downloaded in full and is not a thesis. This research searched articles through the Google Scholar database, Garuda Portal and Research Gate. As a result of the review of the 7 articles, it is known that inaccurate diagnosis codes in obstetric cases are caused by 7 different factors. The most influential factors are information in MRD (Medical Record Document) is written as unclear or incomplete. The second reason is MRD is not double-checked or inspected and the last is code errors in categories and sub-categories.